Chinese bridge : summer camp for international students. ([China] : The Office of Chinese Language Council International and China Central Television, 2007)
Reseña de la visita de estudiantes de Estados Unidos, Canadá y Korea a China
Producer Xu Lin, Zhao Guocheng ; film director Guang Qing ; director of photography, Zhan Jijun, Cui Bo ; editor, Jiang Cuihua, Cui Guofang, Song Bielli
Host: Ji Xiaojun, Guan Qing
Keywords: ESTUDIANTES EXTRANJEROS -- CHINA; ESTUDIANTES UNIVERSITARIOS -- CHINA; CAMPAMENTOS -- CHINA